2015
DOI: 10.1136/heartjnl-2014-306782
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic predictors of major cardiac events in patients with Anderson–Fabry Disease

Abstract: AFD is associated with a high burden of cardiac morbidity and mortality. Adverse cardiac outcomes are associated with age, global disease severity and advanced cardiac disease but not the presence of cardiac genetic variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 22 publications
3
85
2
2
Order By: Relevance
“…Recently, an observational study by Patel et al conducted in AFD patients showed the following incidence rates: 1.62/100 person-years for HF, 1/100 person-years for atrial fibrillation and 0.52/100 person-years for overall death [73].…”
Section: Infiltrative Diseases Anderson-fabry's Diseasementioning
confidence: 96%
“…Recently, an observational study by Patel et al conducted in AFD patients showed the following incidence rates: 1.62/100 person-years for HF, 1/100 person-years for atrial fibrillation and 0.52/100 person-years for overall death [73].…”
Section: Infiltrative Diseases Anderson-fabry's Diseasementioning
confidence: 96%
“…In the study by Patel and colleagues, QRS duration was a significant independent predictor of the primary endpoint; a value ≥120 ms had a positive predictive value of 88% with a negative predictive value of 41% for the occurrence of the composite primary endpoint 5. While QRS duration is often increased in parallel with cardiac hypertrophy, indexed ventricular mass is an independent predictor of atrial fibrillation and the only predictor of cardiac death 5…”
Section: Cardiac Prognosis Is Related To Overall Disease Severity/durmentioning
confidence: 98%
“…The objective of the study was to compare the prognosis of FD in patients ≥16 years with the classic form (multiorgan involvement, n=149) versus patients with mutations ((p.Asn215Ser), (p.Met296Val), (p.Gln279Glu), (p.Arg301Gln), (p.Met296Ile), (p.Ile91Thr), (p.Phe113Leu), (p.Arg112His), (p.Gly328Arg) and the ‘Chinese’ IVS4+919A>G intronic mutation) previously associated with a cardiac prominent/exclusive phenotype (‘cardiac variants’) (n=58) 5. The primary aims were to determine the incidence of a composite (the primary endpoint) of new-onset atrial fibrillation, severe heart failure (New York Heart Association class ≥3), antibradycardia device insertion and cardiac death, and to identify clinical and genetic predictors of those events.…”
Section: Cardiac Morbidity and Mortality Are Remarkably Highmentioning
confidence: 99%
See 2 more Smart Citations